1992
DOI: 10.1152/ajpcell.1992.262.5.c1239
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of force generation and phosphate release in skinned rabbit soleus muscle fibers

Abstract: The kinetics of the force generating and Pi release steps of the actomyosin-adenosinetriphosphatase (ATPase) cycle have been compared in Ca(2+)-activated skinned fibers of rabbit soleus (slow twitch) and psoas (fast twitch) muscle. Pi was rapidly photogenerated within the fiber lattice by laser flash photolysis of caged Pi [1-(2-nitro)phenylethyl phosphate]. Pi reduces isometric tension in the steady state but is less effective in slow-twitch muscle than in fast-twitch muscle (e.g., 14 mM Pi reduces tension by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
78
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 17 publications
21
78
0
Order By: Relevance
“…Thus, having to start from higher initial [P i ] to determine k þPi (2) values at high final [P i ] would change a linear toward a hyperbolic-shaped relation. In line with this idea, an exploration of the k þPi -[P i ] relation over a small [P i ]-range (1-3 mM), by inducing P i -jumps from same initial [P i ] with the caged-P i technique, also yielded a linear relation (17). In summary, when initiated from the same [P i ], P i -induced force kinetics depend linearly on the [P i ].…”
Section: Synthesismentioning
confidence: 81%
See 4 more Smart Citations
“…Thus, having to start from higher initial [P i ] to determine k þPi (2) values at high final [P i ] would change a linear toward a hyperbolic-shaped relation. In line with this idea, an exploration of the k þPi -[P i ] relation over a small [P i ]-range (1-3 mM), by inducing P i -jumps from same initial [P i ] with the caged-P i technique, also yielded a linear relation (17). In summary, when initiated from the same [P i ], P i -induced force kinetics depend linearly on the [P i ].…”
Section: Synthesismentioning
confidence: 81%
“…There is a tendency for the k þPi -[P i ] relation to become more hyperbolic with increasing temperature (13). In contrast, P i -jump studies on slow skeletal muscle fibers (17) and skinned cardiac myocyte bundles (16) revealed linear relations. Similarly, here with cardiac myofibrils, k þPi(2) increased linearly with the final [P i ].…”
Section: Synthesismentioning
confidence: 98%
See 3 more Smart Citations